2018
DOI: 10.9744/jti.20.1.33-48
|View full text |Cite
|
Sign up to set email alerts
|

Curriculum Assessment of Higher Educational Institution Using Trace-segmented Clustering

Abstract: Curriculum mining is research area that assess students’ learning behavior and compare it with the curriculum guideline. Previous work developed sequence matching alignment approach to check the conformance between students’ learning behavior and curriculum guideline. Considering only the sequence matching alignment is insufficient to understand the patterns of group of students. Another work proposed an approach by aggregating the students’ profile to represent students’ learning behavior and investigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Several works have been conducted on analyzing the students' performance in the coherent vertical curriculum by using cluster analysis both on aggregated and segmented data [5], [10]. There is also research implementing the cluster evolution analysis to analyze the migration of the students' learning behavior [6].…”
Section: Educational Data Miningmentioning
confidence: 99%
See 2 more Smart Citations
“…Several works have been conducted on analyzing the students' performance in the coherent vertical curriculum by using cluster analysis both on aggregated and segmented data [5], [10]. There is also research implementing the cluster evolution analysis to analyze the migration of the students' learning behavior [6].…”
Section: Educational Data Miningmentioning
confidence: 99%
“…In this type of curriculum, the student needs to take the course exactly like in the curriculum guideline because there are academic standards to be achieved when student finished all course in the curriculum [4]. Indonesia is one of the countries that applied this type of curriculum to comply with the government guideline of standard competencies [5]. However, there are differences between students learning behavior with the curriculum guideline caused by various reason such as student failing the course, taking incoming courses in advanced, or credit limitation that prohibit student to take more course in particular semester.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the students could be grouped into various clusters per semester that have different learning behavior and performance characteristics. However, the method cannot show the changes in students' learning behavior in a timely manner (e.g., from one semester to another semester) (Priyambada et al, 2018).…”
Section: B Trace-based Clustering and Cluster Evolution Analysismentioning
confidence: 99%
“…In the domain of EPM, the event log can be partially cut in accordance with the timestamp (i.e., period of study or semester). While work has been conducted on trace clustering in the domain of EPM [15], no studies have shown how temporal cases (i.e., students' profiles) changed over time. Most EPM emphasizes the discovered process model, i.e., the model representing students' behavior during the study period.…”
Section: Introductionmentioning
confidence: 99%